Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Pakistan - Lan, Tianqi; Yao, Zhiyuan; Ali, Abid; Zheng, Guo; Li, Shuqiang (Zootaxa, 2020)
The genus Pholcus Walckenaer, 1805 is reported from Pakistan for the first time. Two new species of the Pholcus nenjukovi species-group are described: Pholcus hamuchal Yao & Li sp. nov. (Gilgit Baltistan, male and female) and Pholcus kalam Yao & Li sp. nov. (Khyber Pakhtunkhwa, male and female). Type material is deposited in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) in Beijing, China.